Meningkatkan Kemampuan Keaksaraan Menggunakan Metode Teka-Teki Gambar Pada Anak Usia 5-6 Tahun Di PAUD Nusa Indah Kebon Jeruk Jakarta Barat - Rahmawati , Vivi; Hamidah , Agustin; Rizawati, Rizawati (Jurnal Pendidikan, Sains Dan Teknologi, 2024)
Improving Literacy Skills Using the Picture Puzzle Method in Children Aged 5-6 Years at PAUD Nusa Indah Kebon Jeruk West Jakarta". Thesis. Bekasi: Faculty of Education, Panca Sakti University, Bekasi, 2024.  This study aims to improve the literacy skills of children aged 5-6 years using the picture puzzle method at PAUD Nusa Indah Kebon Jeruk West Jakarta. The research methodology used is classroom action research (CAR) which is carried out in 2 cycles, each cycle consisting of the planning, action, observation and reflection stages. Data collection in this study used observation sheets. From the results of this study, an increase was obtained in each cycle. In cycle I there was an increase of 60% or 6 children, in cycle II there was an increase of 80% or 8 children. So this study was successfully carried out to improve literacy skills using the picture puzzle method in children aged 5-6 years at PAUD Nusa Indah Kebon Jeruk West Jakarta.